Mexico - 2022 Investment Policy and Regulatory Review (Investment Climate Assessment, 2022)
This Investment Policy and Regulatory Review (IPRR) is organized as follows: section two provides an overview of the country's investment policy framework, including the legal instruments regulating foreign investment, key institutions involved in investment promotion, as well as the country's foreign investment promotion strategy; it also delineates the country's international investment legal framework, including the country's commitments under the World Trade Organization (WTO) and select international investment agreements (IIAs); sections three-six cover the country's policies and domestic legal framework concerning different dimensions of the lifecycle of an investment: entry and establishment (section three), protection (four), incentives (five) and linkages (six); sections seven and eight explore emerging investment policy and regulatory areas, section seven considers outward FDI and section eight responsible investment; section nine focuses on city-specific investment policy and regulatory measures in the largest commercial center; and section 10 covers FDI in the digital economy